Total Intravenous Anesthesia with Propofol Associated with Fentanyl, Lidocaine or Ketamine in Bitches Submitted to Elective Ovariohysterectomy - Monzem, Samuel; Spiller, Paulo Roberto; Dower, Nathalie Bassil Moro; Gomes, Lianna Ghisi; Stocco, Matias Bassinello; Oliveira, Anderson Soares Castro de; Flôres, Fabiola Niederauer; Guimarães, Luciana Dambrósio (Acta Scientiae Veterinariae, 2017)
Background: Total intravenous anesthesia with propofol is an alternative to inhalation anesthesia because it offers smoother anesthetic recovery, however, since propofol does not have adequate analgesic action, it is necessary to associate it with some drug to avoid the pain process. In addition, the combination may minimize cardiovascular depression resulting from continuous infusion of propofol by reducing infusion rate. The aim of this study was to evaluate cardiorespiratory parameters and anesthetic recovery in bitches submitted to continuous infusion of fentanyl, lidocaine and ketamine associated with total intravenous anesthesia with propofol and submitted to elective ovariohisterectomy. Materials, Methods & Results: Twenty-four bitches were medicated intramuscularly with 0.03 mg/kg of acepromazine. After 30 min, they were divided into three groups with different analgesic treatments: group F (GF) received a loading dose (LD) of 0.0036 mg/kg fentanyl, followed by continuous infusion of 0.0036 mg/kg/h; group L (GL), LD of 3 mg/kg lidocaine, followed by 3 mg/kg/h and group K (GK), LD of 0.6 mg/kg ketamine, followed by 0.6 mg/kg/h. First a LD of analgesic treatment was administered, followed by induction (to the effect) and beginning of continuous infusion of the analgesic treatment and propofol. The animals were intubated with endotracheal tube of adequate size, and connected to 100% oxygen, being kept under spontaneous ventilation during the entire period of anesthetic maintenance. The infusion of propofol started at 0.34 mg/kg/min and was adjusted so as to maintain the surgical anesthesia plane of Guedel and the cardiovascular parameters within the physiological limits for the species. The cardiorespiratory parameters were measured at different moments: basal (before application of any drug) and 5, 15, 20, 30, 40, 50, 60, 70 and 80 min after induction. The surgery started 20 min after anesthetic induction and lasted 60 min. At the end of the surgery, infusions were terminated and anesthesia recovery was evaluated by measuring the extubation time, sternal decubitus, and quadrupedal position in min. A variance analysis was performed to compare means of cardiorespiratory parameters for the moments and groups followed by the Scott-knott test. Differences were considered significant when P < 0.05. The baseline parameters, age, weight and dose of propofol IC were not statistically different between groups. The infusion rate of propofol increased in all groups from M5 to M15. GF and GL presented lower values for heart rate and GK presented higher values for the same variable. Blood pressure decreased after induction and increased in M40, M50 and M60. The variables EtCo2, PaCo2 and HCO3 increased and pH decreased showing respiratory depression in all groups. The mean time, in min, for orotracheal extubation, sternal decubitus and quadrupedal position were respectively 5 ± 3, 20 ± 6 and 39 ± 13 for GF; 6 ± 2, 23 ± 7 and 51 ± 15 for GL; 4 ± 2, 18 ± 6 and 42 ± 22 for GK and did not present statistical difference between the groups. Discussion: The combination of continuous infusion of fentanyl, lidocaine or ketamine to total intravenous anesthesia with propofol provides cardiovascular stability, but does not prevent respiratory function depression. The dose of propofol IC was the same in all groups, thus demonstrating that analgesics have the same potency in the transoperative period and justifies similar anesthetic recovery times. Thus, it can be concluded that these associations are feasible for total intravenous anesthesia provided proper monitorins for respiratory function.